Planificación de Parques Eólicos en la Región Sur de Ecuador mediante Sistemas de Información Geográfica - Illescas Astudillo, Cristian Javier (2022)
Along this document, a methodology whose objective is to identify the southern Ecuador wind farm optimal placement, is proposed. In order to achieve the stated objectives, it is applied multicriteria analysis together with geographic information system provided tools. The document is structured by: the theoretical knowledge on which the implemented processes are based, the carried-out sequence processes, and the achieved results. The optimal placement selection was achieved through a spatial analysis in which wind farm installation identified variables were classified as limitations or circumstances, depending on the potential impact. Then, these criteria are evaluated, scored, and weighted; followed by the induvial factor’s weights sum, a map algebra process, and a suitable alternative to choose the best location. Keywords: Spatial analysis, geographic information system (GIS), methodology, wind farm